2019
DOI: 10.1016/j.ijrobp.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Chest Wall Toxicity After Stereotactic Body Radiation Therapy: A Pooled Analysis of 57 Studies

Abstract: This study analyzes the significance of clinical and dosimetric risk factors in relation to chest wall (CW) injury after stereotactic body radiation therapy for lung tumors. Our study shows that female sex, having a tumorto-CW distance of <16 to 25 mm, and the dosimetric parameters of maximal dose to 0.5 to 5 cm 3 and 30-Gy volume exposure of CW or rib are risk factors that predict CW toxicity. Purpose: The significance of clinical and dosimetric risk factors in relation to chest wall (CW) injury after stereot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…The rate of grade 3 chest wall toxicity with SABR from a large meta-analysis (combining several different dose and fractionations) is 1.2% [10]. Individual papers have found that the tumour to chest wall distance is a significant factor, as well as the maximum dose (Dmax) and the volume of chest wall receiving 30 Gy (V30) [11e14].…”
Section: Evidencementioning
confidence: 99%
“…The rate of grade 3 chest wall toxicity with SABR from a large meta-analysis (combining several different dose and fractionations) is 1.2% [10]. Individual papers have found that the tumour to chest wall distance is a significant factor, as well as the maximum dose (Dmax) and the volume of chest wall receiving 30 Gy (V30) [11e14].…”
Section: Evidencementioning
confidence: 99%
“…Stereotactic body radiation therapy (SBRT) involving extreme hypofractionation with high-dose radiation to the target volume and low doses to the surrounding normal tissues is considered superior compared with EBRT. However, SBRT is most suitable for small lesions (typically <5 cm), and the accuracy and reproducibility of treatments are essential (24,25). In addition, SBRT is contraindicated for lesions within 2 cm from the bronchial tree, and a marked prevalence of complications such as pulmonary toxicity and rib toxicity have been reported (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, SBRT is most suitable for small lesions (typically <5 cm), and the accuracy and reproducibility of treatments are essential (24,25). In addition, SBRT is contraindicated for lesions within 2 cm from the bronchial tree, and a marked prevalence of complications such as pulmonary toxicity and rib toxicity have been reported (24,25). 125 I seed implantation is a minimally invasive treatment for tumors that has been rapidly developed in the past decade and has been listed as a treatment for prostate cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…This approach (DCA as opposed to VMAT or IMRT) was preferred for many patients whose DCA plans met institutional dosimetric constraints, as the delivery time is relatively fast (<2 minutes) in part assisted by the auto setup of gantry and couch, so that the possibility of respiratory baseline shifts is minimized [16]. The constrains were V20 Gy < 10% for total lung minus GTV, ≤30 Gy max for spinal cord, ≤40 Gy max for esophagus, and V30 Gy ≤ 30 mL for chest wall (CW) [17]. They were practically relevant and used across all patients at our institution.…”
Section: ) Patient Selectionmentioning
confidence: 99%